Ensaio clínico de fase II com Panax ginseng C. A. Meyer no tratamento da síndrome do intestino irritável - Rocha, Heraldo Arcela de Carvalho (2014)
The irritable bowel syndrome (IBS) is defined as the presence of continuing or recurrent abdominal pain or discomfort and it is associated with altered bowel habit. Its pathophysiology involves the following aspects: genetic variables, changes in gut motility and visceral sensitivity, psychosocial factors, in addition to inflammatory and infectious processes. The treatment is based on dietary guidance and change in lifestyle. The use of drugs is indicated in symptomatic stages of IBS. The growing interest of patients for complementary and alternative medicine has been observed in recent years. Panax ginseng C.A. Meyer has been used for centuries in oriental medicine. Experimental studies have demonstrated the antinociceptive action of this herbal medicine on calcium and sodium channels, as well as on primary sensory neurons. The study aimed to: conduct phase II clinical trial with Panax ginseng CA Meyer in patients with IBS; contribute to the study of the pharmacological effects of Panax ginseng C.A. Meyer; evaluate the therapeutic efficacy of Panax ginseng C.A. Meyer in abdominal pain control in patients with IBS; and observe the adverse effects. Twenty-six patients were selected by means of the inclusion criteria for the study and they were divided into two groups. A clinical double-blind, randomized, prospective and experimental trial was conducted for eight weeks, comparing the action of dry extract of Panax ginseng (300 mg / day) with trimebutine (600 mg / day). Abdominal pain was assessed using the Likert scale. Patients were assessed at four visits and the results were analyzed using the Mann-Whitney and Friedman tests, with a significance level of p < 0.05. Twenty- four patients completed the study, being 87.50% female and mean age of 47.41 years. There was a relative homogeneity among patients with regard to sex, age and duration of symptoms. All patients, before beginning treatment with Panax ginseng and trimebutine, had negative scores for the Likert scale values. There was improvement in abdominal pain, through this scale, in patients who used Panax ginseng. This group started from a median basal of -5 to 2.5, 3 and 5 in the 1st, 4th and 8th weeks of treatment, respectively, with a statistically significant difference. Similar results were achieved in the group that used the trimebutine. The only adverse effect observed was the occurrence of headache in two patients (16.66%) in the group that used the herbal. Panax ginseng C.A. Meyer was effective in the control of abdominal pain in IBS patients, analogous to trimebutine, and may be used in future studies, with the prospect of a phase III clinical trial.